Peace, Justice and Strong Institutions - Leal Filho, Walter; Azul, Anabela Marisa; Brandli, Luciana; Lange Salvia, Amanda; Özuyar, Pinar Gökcin; Wall, Tony (Encyclopedia of the UN Sustainable Development Goals, 2020)
text